PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS VI SD - Nofitri Purba; Kadek Yudiana; I Nyoman Tri Esaputra (LPPM Universitas Nias Raya, 2026)
This development research was conducted to address the problem of low learning outcomes among sixth-grade students, which was caused by the limited use of innovative and interactive instructional media. The objectives of this study were to: (1) describe the design of the instructional video; (2) determine its validity; (3) examine its practicality; and (4) evaluate its effectiveness. This study employed a Research and Development (R&D) approach using a One Group Pretest-Posttest design and the 4D development model. The subject of this research was the instructional video, with 35 sixth-grade students involved in the field trial. The objects of the study included the validity, practicality, and effectiveness of the instructional video. Data were collected through observation, interviews, and questionnaires. The data were analyzed using descriptive qualitative and quantitative analysis techniques. The results showed that: (1) the study successfully developed a problem-based learning instructional video on the topic of the impact of human activities on the environment; (2) the material expert validation obtained an average score of 4.6 (very good category), and the media expert validation obtained an average score of 4.8 (very good category); (3) the average practicality score from the teacher practitioner was 4.70 and from students was 4.67 (both in the very good category); and (4) the effectiveness test indicated a significance value (2-tailed) < 0.05, meaning that H₁ was accepted and H₀ was rejected. This indicates that the problem-based learning instructional video is effective in improving students’ learning outcomes. Based on these findings, it can be concluded that the developed instructional video is appropriate for use as a more engaging and interactive learning medium capable of improving students’ learning outcomes.